Strategy formation process of a non-profit organization: The strategy formation process of The Student Union of the University of Vaasa in 2015 - Kyrö, Aino (My University, 2017)
The importance of strategy is understood widely, however, the term strategy can be interpreted and approached in several different ways. Strategy can be seen as a guideline that guides the organization. The purpose of a strategy is to help organization to succeed to fulfil its purpose of existence. Leadership and strategy formatting is as important in public sector as in private sector. The fields are different, therefore the processes and goals vary, however, the importance is the same. All organizations have to have clear reasons for their existence and goals to further. Strategies can be seen as deliberate, emergent or unrealized. Usually strategies involve aspects from each of the kinds. Deliberate strategies are planned actions, whereas emergent strategies evolve during the process. The Student Union of the University of Vaasa is a non-profit organization which purpose is to supervise the interests of the students and to act as a link between the students and the University of Vaasa. This thesis concentrates on the research question: How key features of different schools of strategy can be seen in the strategy process of The Student Union of the University of Vaasa? The thesis focuses on the strategy formation process of The Student Union of the University of Vaasa in 2015. A successful strategy process ought to include aspects from different schools of strategic management. In the strategy process of The Student Union of the University of Vaasa one can distinguish aspect from not only one school of strategic management, but from many of them. The strategy formation process of The Student Union of the University of Vaasa in 2015 included a strategy inquiry. The data collection method used in the strategy inquiry of The Student Union of the University of Vaasa was a role-playing method which is an interesting way to get the insight from the respondents.
Keywords: strategy; strategy process; non-profit organization; fi=Julkisjohtaminen|en=Public Management |; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|